Strengthening 21st-Century Education Themes in ELT Material for ESP Students - Sebastianus Menggo (VELES Voices of English Language Education Society, 2022)
Needs analysis is essential in designing English materials. A powerful teaching-learning tool for practitioners, it allows them to produce English resources linked to students' needs. It is therefore viewed as an essential part of the teaching process for conducting need analysis. This study aims to expose academic studies related to the types of teaching materials and learning activities desired by students. This study examined 232 students enrolled in five different study programs of Universitas Katolik Indonesia Santu Paulus Ruteng. The instruments were questionnaire and interview, then the data were analyzed using a software program, namely an excel chart data series. The findings revealed that the types of teaching materials and learning activities required by students highlighted the importance of providing English materials in promoting 21st-century education themes. English materials should be adapted to match the needs of students, with an emphasis on the six themes of 21st-century education themes, such as global awareness, financial literacy and entrepreneurship, civic, health, digital, and environmental literacy.